Effect of a Waterproof Device in the Noninvasive Ventilation Circuit on patient-machine Synchronization - Hu Jieying; Zheng Zeguang; Yang Feng; Zhong Lihong; Chen Rongchang (Journal of Respiratory Diseases, 2017)
Objective Investigate the effect of connecting a waterproof device at the front end of the piezometric tube on pressure transmission and patient-machine synchronization during the noninvasive ventilation. Method In test 1, the waterproof device was connected to the piezometric tube and put into a closed container, the pressure inside the container was varied to observe the corresponding pressure change in the piezometric tube. In test 2, a waterproof device was connected in front of the piezometric tube during noninvasive ventilation.12 subjects were received noninvasive ventilator so that dynamic changes of the pressure inside the mask (Pmask) and piezometric tube (Ptube) could be measured. Results In test 1, when the pressure in the container was gradually increased to 50 cmH2O and then decreased to 0, the pressure inside the piezometric tube changed synchronously with the pressure inside the container, with no statistically significant difference between the pressures (0.009 ± 0.138) cmH2O. In test 2, there was no significant increase in triggering time, pressure, and power after connecting the waterproof device at the front end of the piezometric tube. There was no significant difference in the platform pressure and baseline pressure as measured by Pmask, before and after connecting the waterproof device. Finally, there was no significant difference in the platform pressure and baseline pressure between Pmask and Ptube after connecting the waterproof device.
Keywords: respiration